Clinical outcome of pediatric patients using polymyxin B - da Costa, Jocasta; Amaral Boa Sorte, Ney Cristian; de Moura Santos, Pablo (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
ABSTRACT Objective: to evaluate the clinical effectiveness and safety of polymyxin B in the treat ment of infections caused by bacteria resistant to multiple drugs. Methods: a retrospec tive cohort was carried out, evaluating the medical records of diagnosed patients with infections caused by bacteria resistant to multiple drugs and treated with polymyxin B (from January 2018 to December 2020, in intensive care units of a pediatric hospital in Salvador – Ba. Safety was assessed using the nephrotoxicity criteria established by Kid ney Disease: Improving Global Outcomes. Results: a total of 39 patients used polymyxin B for infections caused by bacteria resistant to multiple drugs, with treatment success being achieved in 13 (33.3%) patients with clinical and/or microbiological cure, while the Mortality was observed in 26 (66.6%) patients, of which 19 (73%) were described in a medical report as death related to infection and 7 (27%) were associated with complications from comorbidities. The occurrence of kidney injury was reported in 21 patients, of which 6 were discarded to do renal damage before the use of polymyxin B, 15 (38.4%) with a rate of nephrotoxicity classified as stages 1, 2, and 3, according to the Kidney Disease: Improving Global Outcomes criteria. Conclusion: approximately one third of patients were clinically and microbiologically cured. It is necessary to carefully evaluate treatment with polymyxin B, prioritizing multidrug-resistant infections, rational use and attention to monitoring renal function. Keywords: multidrug resistance; polymyxin B; drug toxicity; child; Bacterial resistance.